2009
DOI: 10.1158/1535-7163.mct-09-0214
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of transcription by the peroxisome proliferator-activated receptor δ–binding RNA aptamer in colon cancer cells

Abstract: Peroxisome proliferator-activated receptor δ (PPAR-δ), one of three PPAR subtypes, is a lipid-sensing nuclear receptor that has been implicated in multiple processes, including inflammation and cancer. To directly establish the role of PPAR-δ in colon cancer development and progression, we selected high-affinity RNA aptamers and expressed them in several colon cancer cell lines. Nuclear-expressed aptamers efficiently inhibited PPAR-δ-dependent transcription from a synthetic peroxisome proliferator response ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Complex networks with other signaling pathways could provide a way to reconcile contradictory results from different systems (25,56,57). Interplay with ␤-catenin signaling might be reasonable, because of cancerspecific activation of ␤-catenin (50,58,59), association with PPAR-␦ overexpression (26,60,61), and cross-talk between TCF/␤-catenin signaling and PPAR expression and activity (62, 63). Here, we provide evidence that PPAR-␦ acts on the VEGFA gene along with ␤-catenin by regulating chromatin loops.…”
Section: Discussionmentioning
confidence: 99%
“…Complex networks with other signaling pathways could provide a way to reconcile contradictory results from different systems (25,56,57). Interplay with ␤-catenin signaling might be reasonable, because of cancerspecific activation of ␤-catenin (50,58,59), association with PPAR-␦ overexpression (26,60,61), and cross-talk between TCF/␤-catenin signaling and PPAR expression and activity (62, 63). Here, we provide evidence that PPAR-␦ acts on the VEGFA gene along with ␤-catenin by regulating chromatin loops.…”
Section: Discussionmentioning
confidence: 99%
“…Another related mechanism is derived from the observation that ligand activation of PPAR β / δ increases the expression of VEGF through a PPAR β / δ -dependent mechanism, causing increased phosphorylation of AKT, which promotes cell survival by blocking apoptosis [127]. In addition, Kwak et al [128] demonstrated that PPAR β / δ -binding aptamers suppressed transcription from natural promoters of VEGF-A and COX-2 and inhibited tumorigenic potential of colon-cancer cells. These data suggest that PPAR β / δ play an important role in transcription of tumor-promoting genes such as VEGF-A and COX-2.…”
Section: The Role Of Pparβ/δ In Colorectal Cancermentioning
confidence: 99%
“…GW and related agonists enhance adenoma size and angiogenesis in APC min mice (9, 10) and stimulate the growth of several lung (11), breast and prostate cancer cell lines (12, 13), although results to the contrary have also been reported (14). Conversely, disruption of PPARδ expression in colon cancer cells by somatic cell knockout (15) or RNA aptamers (16) inhibited tumor cell growth. These findings are consistent with those demonstrating that homozygous deletion of PPARδ reduces tumorigenesis in MMTV-Cox2 mice (17), intestinal adenomas in APC min mice (18), colon carcinogenesis (19) and pancreatic tumor xenograft growth and angiogenesis in stromal tissue (20).…”
Section: Introductionmentioning
confidence: 99%